2015
DOI: 10.1017/neu.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Dietary magnesium deficiency alters gut microbiota and leads to depressive-like behaviour

Abstract: ObjectiveGut microbiota (GM) has previously been associated with alterations in rodent behaviour, and since the GM is affected by the diet, the composition of the diet may be an important factor contributing to behavioural changes. Interestingly, a magnesium restricted diet has been shown to induce anxiety and depressive-like behaviour in humans and rodents, and it could be suggested that magnesium deficiency may mediate the effects through an altered GM.MethodsThe present study therefore fed C57BL/6 mice with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
56
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 50 publications
(61 reference statements)
1
56
1
Order By: Relevance
“…Recent scientific reports have suggested that gut microbes affect many metabolic processes of the host, including its mineral metabolism. The microbiota is involved in the metabolism of calcium, iron, magnesium, selenium, copper, zinc and silver . Both in vitro and animal investigational models are in use.…”
Section: Introductionmentioning
confidence: 99%
“…Recent scientific reports have suggested that gut microbes affect many metabolic processes of the host, including its mineral metabolism. The microbiota is involved in the metabolism of calcium, iron, magnesium, selenium, copper, zinc and silver . Both in vitro and animal investigational models are in use.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of serum Mg 2+ have been suggested to play a role in the biological dysregulation contributing to depression. Experimentally induced Mg 2+ deficiency resulted in depression-like behavior in mice [4], and a recently study suggested that an antidepressant-like activity of Mg 2+ in an animal model of anhedonia for the first time [5]. In addition, a growing body of evidence indicated an inverse relationship between Mg 2+ intake and the risk of stroke [6-9].…”
mentioning
confidence: 99%
“…A diet deficient in Mg, increased depressive-like behaviour and altered the gut microbiota, which suggested that magnesium deficiency could be a mediator of the behavioural effects through an altered gut microbiota [61]. Interestingly, a significant correlation was found between the gut microbiota of the diet deficient in Mg and a decrease in hippocampal IL-6 levels, suggesting that this immunemodulation could be the mechanism by which diet induced changes in the gut microbiota composition alter behaviour [61]. A similar study found that a diet deficient in Mg decreased bacterial diversity and altered anxiety-like behaviour [62].…”
Section: Dietary Interventionsmentioning
confidence: 99%